A quasi‐global assessment of changes in remotely sensed rainfall extremes with temperature. Issue 24 (30th December 2016) - Wasko, C.; Parinussa, R. M.; Sharma, A.
Abstract: The dependence between extreme rainfall and temperature is used to understand climatic relationships, constrain model predictions, and evaluate future changes to rainfall. Understanding this dependence, however, is limited by the fact that many areas worldwide lack gauged data, particularly at short time scales. The advent of remote sensing allows a new insight into this dependence quasi‐globally. Here we address whether remotely sensed daily rainfall and temperature can be used in ungauged areas to understand extreme rainfall scaling with temperature. Using the multisensor Tropical Rainfall Measuring Mission 3B42 (v7) rainfall product and remotely sensed air temperature, we examine the spatial homogeneity in remotely sensed rainfall scaling with temperature and demonstrate that it replicates the spatial variation in the scaling observed in ground data. Finally, changes to duration and percentile are examined showing that the scaling response is climatologically sensitive. Key Points: The dependence of rainfall to temperature in remotely sensed products is compared to ground observations Spatial inhomogeneity in the dependence of rainfall on temperature is preserved in remotely sensed products Sensitivities to duration and percentile are explored